2019
DOI: 10.1016/j.bbamcr.2018.07.021
|View full text |Cite
|
Sign up to set email alerts
|

The role of pseudophosphatases as signaling regulators

Abstract: Pseudophosphatases are atypical members of the protein tyrosine phosphatase superfamily. Mutations within their catalytic signature motif render them catalytically inactive. Despite this lack of catalytic function, pseudophosphatases have been implicated in various diseases such as Charcot Marie-Tooth disorder, cancer, metabolic disorder, and obesity. Moreover, they have roles in various signaling networks such as spermatogenesis, apoptosis, stress response, tumorigenesis, and neurite differentiation. This rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
93
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(96 citation statements)
references
References 67 publications
1
93
0
Order By: Relevance
“…This report investigated the effects of the pseudophosphatase MK-STYX on HDAC6. Because both HDAC6 and MK-STYX interact with the stress granule nucleator G3BP-1 and they have antagonistic roles in stress granule formation, promotion and inhibition [4,28], it was important to determine whether MK-STYX affects HDAC6 subcellular location and phosphorylation state, as well as the post-translational modification of its substrate, microtubules. We showed that MK-STYX caused a proportion of this cytosolic protein to localize in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This report investigated the effects of the pseudophosphatase MK-STYX on HDAC6. Because both HDAC6 and MK-STYX interact with the stress granule nucleator G3BP-1 and they have antagonistic roles in stress granule formation, promotion and inhibition [4,28], it was important to determine whether MK-STYX affects HDAC6 subcellular location and phosphorylation state, as well as the post-translational modification of its substrate, microtubules. We showed that MK-STYX caused a proportion of this cytosolic protein to localize in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…MK-STYX (MAPK (mitogen-activated protein kinase) phosphoserine/threonine/tyrosine-binding protein) is a catalytically inactive member of the protein tyrosine phosphatase (PTP) superfamily, classified as a pseudophosphatase [1,2,3,4]. In MK-STYX, critical histidine and cysteine residues in its PTP active site signature motif (HCX 5 R), which are essential for phosphatase activity, are replaced by phenylalanine and serine residues (FSTQGISR) [1,2,3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations